2011
DOI: 10.1016/j.febslet.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes as a new source of catecholamine production

Abstract: a b s t r a c tCatecholamines are an important regulator of lipolysis in adipose tissue. Here we show that rat adipocytes, isolated from mesenteric adipose tissue, express genes of catecholamine biosynthetic enzymes and produce catecholamines de novo. Administration of tyrosine hydroxylase inhibitor, alpha-methyl-p-tyrosine, in vitro significantly reduced concentration of catecholamines in isolated adipocytes. We hypothesize that the sympathetic innervation of adipose tissues is not the only source of catechol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 26 publications
3
63
0
4
Order By: Relevance
“…NE that is produced mostly by the sympathetic nerves remained unchanged probably due to the quick physiological mechanisms of NE supplies maintenance consisting of NE turnover regulation. Due to a very high concentration of sympathetic NE stores within the mWAT compared to NE produced by adipose tissue cells such as macrophages or adipocytes (Vargovic et al 2011), it is probably impossible to distinguish the changes in non-sympathetic NE unless the mWAT is separated into the cell fractions (Vargovic et al 2011). However, in our previous study we have described cold-induced elevations of NE and EPI levels in adipocytes and stromal/vascular fractions, obtained from the mWAT by collagenase digestion (Kvetnansky et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…NE that is produced mostly by the sympathetic nerves remained unchanged probably due to the quick physiological mechanisms of NE supplies maintenance consisting of NE turnover regulation. Due to a very high concentration of sympathetic NE stores within the mWAT compared to NE produced by adipose tissue cells such as macrophages or adipocytes (Vargovic et al 2011), it is probably impossible to distinguish the changes in non-sympathetic NE unless the mWAT is separated into the cell fractions (Vargovic et al 2011). However, in our previous study we have described cold-induced elevations of NE and EPI levels in adipocytes and stromal/vascular fractions, obtained from the mWAT by collagenase digestion (Kvetnansky et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…TH, which is the fi rst and rate-limiting enzyme involved in catecholamine biosynthesis, showed increased protein level in response to 1 day (p<0.05) or 7 days (p<0.01) cold exposure. In order to assess de novo synthesis of CAs in the mWAT, we analyzed TH and PNMT gene expression, which may refl ect non-sympathetic sources of CA production in macrophages and adipocytes, as it has been described previously (Nguyen et al 2011;Vargovic et al 2011;Vargovic et al 2013). Real time RT-PCR analysis revealed that 7 days cold induced a rise of TH (p<0.01) and PNMT (p<0.05) expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations